Measurement Effects and the Variance of Returns After Stock Splits and Stock Dividends - Koski, Jennifer Lynch (Review of Financial Studies, 1998)
This article examines the relation between two factors affecting stock returns, the bid-ask spread and price discreteness, and the increase in return variance after ex-dates of stock splits and stock dividends. Controlling for these effects, the variance of daily returns still increases significantly. The variance of weekly returns also increases significantly, and the variance of returns for a control sample of nonsplitting firms shows no significant increase. Variance ratio tests show that bid-ask errors are small for these stocks and therefore cannot explain the large increase in variance. Spreads and price discreteness do not explain increased variance after stock distributions.